Pemberdayaan Perempuan di Masa Pandemi: Studi Kelompok Wanita Tani (KWT) Silih Asih Sindangjawa, Kuningan - Istiqomah, Istiqomah (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2021)
Women's empowerment has been carried out in several programs in Indonesia. This research will look at the empowerment model carried out by the village government of Sindangjawa through the women's empowerment program at the Silih Asih Farmer Group. This research method uses a qualitative approach with purposive sampling and data retrieval techniques using interviews, observation and documentation study. The results of this study indicate that the three models of empowerment, both local development, social planning, and social action as suggested by Hikmat are in accordance with existing conditions in the field.